Metabolic features of qualified academic woman rowing in the boat and on the rowing machines - Kvashuk P.V.; Voronov A.V.; Ryzhikova N.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the features of metabolic support for rowing by qualified academic women in a boat and on rowing ergometers, taking into account the pace of exercises. Methods and structure of the study. The indicators reflecting the metabolic characteristics of qualified female academics were studied when rowing at different rates (22-24 strokes/min; 26-28 strokes/min; 30-32 strokes/min), in a boat and on the Concept-2 and RP3 rowing machines. Four female academicians qualified as candidate master of sports and master of sports took part in the study. Age – 19.5±2.4 years; body length – 179.5±6.8 cm; body weight – 75.3±12.7 kg. Results and conclusions. It was revealed that when rowing qualified female academics at a rate of 22-24 strokes/min in a boat and on Concept-2 and RP3 ergometers, the criteria for metabolic support of work did not have significant differences. At this pace, the load can be classified as a zone of moderate physiological power. When rowing at a rate of 24-26 strokes/min on rowing ergometers among qualified academicians, the metabolic support criteria for work were significantly higher than when rowing in a boat. Rowing on ergometers at this pace can be classified as a load of high physiological power, and rowing in a boat can be classified as a load of moderate power. When rowing at a rate of 30-32 strokes/min on rowing ergometers, the level of biological stress (internal load) among female academics was significantly higher than when rowing in a boat, and the load should be attributed to the zone of submaximal physiological load. In this case, rowing in a boat can be classified as a zone of high physiological power. Rowing on the Concept-2 and RP3 ergometers for academic women is a more intense exercise compared to rowing in a boat. Performing intense exercises on rowing ergometers involves a significant increase in energy expenditure and, accordingly, recovery time in female athletes.